The Art of Implication: Studying Flouting of Maxims in Comments on Indonesian Instagram Influencer Pages - Anggit Laesa Oktaviani (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2024)
Intstagram is one of social media that is used for communication and dissemination of visual content. Users of Instagram engage in interactions through comments, often employing varied linguistic forms, including ambiguity and slang, for diverse purposes. Despite the intended socialization within the platform, misinterpretation of comment meanings frequently occurs, especially on Indonesian influencers account; prompting this study to explore flouted maxims in Instagram comments and elucidate speakers' implied meanings. Drawing data from Instagram comment sections exhibiting instances of maxim flouting, this research adopts a qualitative descriptive approach underpinned by Pragmatics using the theories of Grice (1975) to categorize the types of maxims and theory by Leech (1983) to explain the reasons in the situation for the netizens in doing the utterances. Through the analysis of five selected datasets, guided by conversational implicature and the cooperative principle, the study unveils the prevalence of flouted maxims, particularly those pertaining to Maxim of Relevance. Furthermore, the analysis reveals that the netizens on instagram primarily mainly uses different context of the utterance and the goal of the utterance